P-D7 Synthesis and Characterization of a Long Acting Nanoformulated Dolutegravir. (March 2017) - Sillman, Brady; Bade, Aditya; Mcmillan, Joellyn; Edagwa, Benson; Gendelman, Howard
Abstract : Dolutegravir (DTG) is a potent integrase strand transfer inhibitor with a unique resistance profile for treatment and prevention of the human immunodeficiency virus type one (HIV-1) infection. With immediate need for long acting antiretroviral drugs (ARVs) in treatment regimens, long acting prodrugs that reduce systemic metabolism and polarity, affect lipophilicity and enhance membrane permeability are of high value. To this end, we synthesized a modified DTG (MDTG) through esterification of the DTG 7-hydroxyl group with myristic acid then confirmed by 1H-NMR and FT-IR spectroscopy. Poloxamer (P407) and folic acid (FA) decorated-P407 nanoformulations were synthesized for both DTG and MDTG to further improve its targeting potential and longevity. Stability, size, shape and charge of the developed nanoformulations were compared against their pharmacokinetic (PK) and biodistribution. All had uniform particle size (237–393 nm) and negative zeta potentials. The nanoformulated MDTG showed >100-fold drug uptake in human monocyte-derived macrophages (MDM) and prolonged cell retention beyond 15 days when compared to native DTG. The results paralleled antiretroviral activities as evidenced by protection of MDM against HIV-1 challenge with the macrophage tropic ADA strain at days 1, 5, 10 and 15 after drug formulation treatment as measured by HIV-1 reverse transcriptase activity and p24 staining. PK testing showed that the drug' half-life was increased from 86 hours for P407-DTG to >223 hours for P407-MDTG with projected drug levels above the IC90 (64 ng/mL) for >8 weeks. These results demonstrate early promise for development of a potent, long-acting parenteral formulation of DTG for the treatment of HIV-1 infection.